2016
DOI: 10.21608/zjar.2016.65547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Substrates and Nutrient Solutions on Vegetative Growth, Mineral Content, Production and Fruit Quality of Strawberry

Abstract: The impact of three substrate mixtures and three nutrient solutions on the vegetative growth, mineral content, production and fruit quality of strawberry (Fragaria×ananassa, cv. Festival) was studied under unheated double-span plastic house conditions, at the Central Laboratory for Agricultural Climate (CLAC), Agricultural Research Center (ARC) during the two winter seasons of 2012/2013 and 2013/2014. The three substrate mixtures were perlite:peat-moss (1:1 V/V) M1, perlite: plant compost (4:1 V/V) M2, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Studies have shown that different substrates can have significant impacts on germination, plant growth, flowering, and fruit quality (Ahmad et al 2012, El-Sayed et al 2016Leroy et al 2017). This is largely because of the difference in factors such as nutrient composition and form, pH, electrical conductivity, and availability of organic compounds (Caballero et al 2007;Ahmad et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that different substrates can have significant impacts on germination, plant growth, flowering, and fruit quality (Ahmad et al 2012, El-Sayed et al 2016Leroy et al 2017). This is largely because of the difference in factors such as nutrient composition and form, pH, electrical conductivity, and availability of organic compounds (Caballero et al 2007;Ahmad et al 2012).…”
Section: Introductionmentioning
confidence: 99%